ANALISIS EMPIRIS HUKUM WAGNER DAN HIPOTESIS KEYNES PADA PEREKONOMOIAN KABUPATEN/KOTA DI PROVINSI PAPUA - Indahsari, Kurniyati; Maryar, Meiske Leno (Journal of Economics Development Issues, 2024)
This study aims to examine Keynes's Hypothesis and Wagner’s Law in the cities and dustricts in Papua Province economy. This study is a quantitative study using data on government spending, real Gross Regional Domestic Product (GRDP), and GRDP per capita of cities and districts in Papua Province in 2010-2020. Panel data regression and Granger Causality testing were used for testing the hypothesis of Keynes and Wagner's Law as well as for proving a two-way relationship between GDRP and government spending. The results show that Wagner's Law does not work at the districts and cities in Papua Province. The regional economic growth doesn’t effect the government spending or public sector share in the regional economy. Furthermore, the Granger Causality Test had proved a one way relationship between government spending on GRDP per capita which's mean the Keynes hypothesis are proved. The government spending increases in order to improve the regional economy in districs and cities in Papua Provinces.